Age Differences in Sarcoidosis Patients with Posterior Ocular Lesions. (August 2014) - Nagata, Kenji; Maruyama, Kazuichi; Sugita, Sunao; Fukuchi, Urara; Terada, Yukiko; Ishizuka, Atsuko; Nakazawa, Toru; Mochizuki, Manabu; Kinoshita, Shigeru
Abstract Purpose: To determine if age- and gender-related differences are correlated with the clinical aspects of posterior ocular lesions in sarcoidosis patients. Methods: Age at disease onset, gender, and ocular findings were obtained from clinical records. Out of the 84 patients enrolled in the study, 22 were 45 years old or younger while 62 were older than 45. After division of the fundus field into three areas, lesion locations were investigated. Results: The mean age of disease onset in the male (44.5 ± 16.8 years) was lower than in the female (55.5 ± 16.8 years). The lesions at the posterior segment in the older patients were found to be located around the peripheral area. However, no statistically significant difference in the location of the lesions was found for gender. Conclusions: There was a statistically significant difference between younger and older sarcoidosis patients for the disease lesions. Lesions were located around the peripheral area at the posterior segment in older patients.